Natural frequency changes due to severe corrosion in metallic structures - Gillich, Gilbert-Rainer (Strojniški vestnik, 2015)
Degradation of engineering structures due to corrosion affects their safety by reducing the cross-section of structural components and altering the material's mechanical characteristics. These parameter changes are observable in the shift of the natural frequencies. In the study presented in this paper, it was demonstrated that the kinetic energy distribution reflects the mass participation, thus being able to predict frequency changes due to mass loss, while the modal strain energy distribution can be properly used to indicate the location of the damage. As a result, two mathematical relations were developed by the authors, predicting the frequency changes due to the main effects of corrosion: loss of mass and loss of stiffness.
Keywords: izguba mase; konzolni nosilec; premik lastnih frekvenc; vrednotenje korozije; zmanjšanje togosti